Torgeir Rebolledo Pedersen and Akin Duzakin: Poems and Unpoems about a little of everything - Atle Krogstad (Barnelitterært Forskningstidsskrift)
In this article, I explore how the relationship between humans and nature is depicted in the illustrated poetry book Poems and Unpoems About a Little of Everything (Pedersen & Duzakin, 2016). Leaning on ecocritical theory and picturebook theory I analyse how the iconotext of the poetry picturebook depicts landscapes, ecosystems and biotopes, and the relationship between human and zoological species that inhabit the landscapes. The illustrated picturebook invites nuanced experiences of nature and digital culture and encourages reflections on and wonder about the interplay and mutual contact between animals and the human species.